Loss analysis and theoretical efficiency limit of monolithic cell. Issue 6 (27th March 2022) - Xue, Shujian; Goryll, Michael; Bowden, Stuart G.
Abstract: Solar cells industries have a trend of making larger wafers, which leads to larger ohmic loss. Halved and shingling cells possess advantages, such as lower ohmic and shading loss, which gives them an advantage over normal solar cells. Monolithic cell resembles halved and shingling cells but without the necessity to cut original cells into strings of smaller cells. The monolithic cell has multiple string cells on the same wafer interconnected with fingers front‐to‐front and back‐to‐back. As a result, the monolithic cell possesses the same advantages while eliminating the cutting‐edge recombination loss. The disadvantage of the monolithic cell is the extra loss caused by the unseparated base region of string cells. In previous studies, efforts have been devoted to reducing this loss by increasing the internal resistance between string cells. In this paper, a quantitative analysis is proposed. It provides means to calculate the effect of different parameters on the extra power loss. Under this guideline, the theoretical minimum extra efficiency loss can also be obtained through directional optimization. As a result, the loss due to the interconnected base region can be further reduced from 1.5% absolute (1.5%abs ) to less than 0.6%abs .